2011
DOI: 10.1002/path.2893
|View full text |Cite
|
Sign up to set email alerts
|

Classical complement activation as a footprint for murine and human antiphospholipid antibody‐induced fetal loss

Abstract: Recurrent miscarriage, fetal growth restriction and intrauterine fetal death are frequently occurring complications of pregnancy in patients with systemic lupus erythaematosus (SLE) and antiphospholipid syndrome (APS). Murine models show that complement activation plays a pivotal role in antiphospholipid antibody-mediated pregnancy morbidity, but the exact pathways of complement activation and their potential role in human pregnancy are insufficiently understood. We hypothesized that the classical pathway woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 32 publications
8
81
1
Order By: Relevance
“…43,44 Recently, in a study of women with SLE and APS, it has been reported that classical complement activation plays a major role in aPL-mediated fetal injury and that placental C4d deposition is a reflection of classical complement activation in women with APS. 12 Similar pathological findings have been reported in endometrium of women with aPL. Although aPL have been reported to activate endothelial cells in vivo, and create a prothrombotic state on endothelial cells, 31 thrombotic occlusion or intimal thickening affecting endometrial blood vessels is not often detected by hematoxylin-eosin staining of specimens from women with aPL.…”
Section: Placental Pathology and Micro-angiopathy Induced By Aplsupporting
confidence: 73%
See 1 more Smart Citation
“…43,44 Recently, in a study of women with SLE and APS, it has been reported that classical complement activation plays a major role in aPL-mediated fetal injury and that placental C4d deposition is a reflection of classical complement activation in women with APS. 12 Similar pathological findings have been reported in endometrium of women with aPL. Although aPL have been reported to activate endothelial cells in vivo, and create a prothrombotic state on endothelial cells, 31 thrombotic occlusion or intimal thickening affecting endometrial blood vessels is not often detected by hematoxylin-eosin staining of specimens from women with aPL.…”
Section: Placental Pathology and Micro-angiopathy Induced By Aplsupporting
confidence: 73%
“…However, recent findings from APS research using animal models have demonstrated that APSinduced obstetrical complications are initiated by inflammation rather than thrombosis. [10][11][12] These studies suggest that anti-inflammatory treatment should be considered for APS management. This review will discuss the characteristics of aPL expression in women with RPL, the potential mechanisms of tissue injury by aPL, how heparin therapy might inhibit the pathogenic mediators of disease, and the management of obstetrical APS.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, mouse models have provided a solid base of the importance of complement activation in successful pregnancies (C3 being a pivotal molecule), as well as its regulation by alias CR1L (complement component (3b/4b) receptor 1-like), sometimes in relation with autoimmune diseases. [40,[141][142][143][144][145] Therefore, while the topic of the present review was human disease, it is clear that much can be understood mechanistically using animal models, especially rodents.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence showing increased C4d deposition in the trophoblast cytoplasma, trophoblastic cell and basement membrane, and extracillous trophoblasts in patients with APAs compared to control patients [36]. Diffuse C4d staining at the feto-maternal interface was present almost exclusively in patients with SLE and/or APS and was related to intrauterine fetal death [37]. Dramatically increased immunohistochemistry staining of C-4d was statistically associated with low-placental weights and low birth weight in SLE patients [38].…”
Section: C4d Deposition In Tissues In Sle Patientsmentioning
confidence: 91%
“…Adverse events during pregnancy [35][36][37] Renal tissue Related to the presence of microthrombosis and histopathological classification of lupus nephritis [38,42] No relationship with disease activity, histological activity and chronicity of lupus nephritis [41,43,44] …”
Section: Placentasmentioning
confidence: 99%